AICCRA 2021 Survey Results - final data - Schuetz, Tonya; Poulos, Allison; Rose, Alison (2022)
Satisfaction Survey that was disseminated to partners to gather their feedback on three of the intermediate Project Indicators (IPI), as laid out in the Project Implementation Arrangements. These indicators capture progress on (1 - IPI 1.3) the satisfaction with the usefulness, accessibility and relevance, particularly for gender and youth responsiveness, (2 - IPI 2.4) effectiveness of partnerships and (3 - IPI 3.3) the use or adaptation of AICCRA-funded climate-relevant knowledge products, decision-making tools and services. The survey was open from 29 January through 9 February 2022 (2022-02)